Free-standing 3D graphene/polyaniline composite film electrodes for high-performance supercapacitors - Wang, Shiyong; Ma, Li; Gan, Mengyu; Fu, Shenna; Dai, Wenqin; Zhou, Tao; Sun, Xiaowu; Wang, Huihui; Wang, Huining (Journal of power sources, 2015)
The research paper describes polyaniline (PANI) nanowires array on flexible polystyrene microsphere/reduced graphene (PS/rGN) film is synthesized by dilute polymerization, and then the PS microspheres are removed to form free-standing three-dimensional (3D) rGN/PANI composite film. The chemical and structural properties of the 3D rGN/PANI film are characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and Brunauer–Emmett–Teller (BET), and the results confirm the 3D rGN/PANI film is synthesized successfully. When the film is used as a supercapacitor electrode, the maximum specific capacitance is as high as 740 F g−1 (or 581 F cm−3 for volumetric capacitance) at a current density of 0.5 A g−1 and the specific capacitance retains 87% of the initial after constant charge–discharge 1000 cycles at current density of 10 A g−1. It is believed that the free-standing 3D rGN/PANI film will have a great potential for application in supercapacitors. [Display omitted] •The 3D rGN/PANI composite film with vertically aligned PANI nanowires is obtained.•Composite film with porous structure can be generated by the removal of PS templates.•The composites film with 3D structure show superior electrochemical performance.